Sistem Informasi Palang Merah Indonesia (PMI) Dengan Menggunakan Visual Basic.Net - Sophian, Sophan (STKIP PGRI Sumatera Barat, 2016)
Indonesian red cross an organization nonprofit having tasks and functions to make public services in socially , health and humanity .But the services in the health sector is blood donating service conducted by a unit blood donation pmi .In the implementation of these services unit blood donation still use a data processing system manually .A data processing system that manual are often have been several issues like processing , search and presentation of data requires a relatively long time and high risk of damage or lose some data for not arranged in orderly and the absence of data base blood donation .So , blood donation service performance by unit the blood donation still has not been effectively and efficiently .In the challenge of increased service performance donor unit of the blood , writer saw the need of attempts to the transformation of a data processing system manually